BURNOUT SYNDROME PADA PERAWAT DI RUANGAN RAWAT INAP RUMAH SAKIT SANTA ELISABETH MEDAN - Lindawati F Tampubolon (Jurnal Keperawatan Priority, 2018)
Burnout syndrome is a response to an emotionally demanding situation with the demands of the recipient who needs the help, attention, and care of the service provider. Burnout have 3 dimensions, they are emotional fatigue, depersonalization, and achievement of the self-achievement. The purpose of this research is to identify burnout syndrome incidence towards nurses in the inpatient room of the Elisabeth Hospital, Medan, 2017. The research is conducted in the Elisabeth Hospital, Medan. This research is descriptive survey design. The research population is nurses who numbered 139 respondents. Sampling technique of simple random sampling has 103 respondents. Data analysis in this research is a univariate analysis. The results show that the majority of nurses on burnout syndrome in the low category are 68 respondents (66%), based on 21-30 year old-majority age are 53 respondents (51.5%), women-majority gender are 62 respondents (60.2%), Diploma III Nurses-majority latest education are 51 respondents (49.5%), majority of unmarried status are 43 respondents (41.7%), and majority of long working for 2-4 years old are 37 people (35.9%). A description of burnout syndrome incidence towards nurses in the inpatient room of the Elisabeth Hospital, Medan, 2017, is in the low category. The results of research are suggested to nurses to train their skills, follow skills training, and maintain effective coping in working.